2018
DOI: 10.1002/bkcs.11596
|View full text |Cite
|
Sign up to set email alerts
|

Template‐assisted Morphological Evolution of Cu2S and Cu2MoS4 from Octahedral Cu2O Crystals

Abstract: Various morphologies of Cu 2 S and Cu 2 MoS 4 were synthesized from an octahedral Cu 2 O template in the presence of various concentrations of sodium molybdate and thioacetamide by carrying out solvothermal reactions in an ethylene glycol solvent. The morphology varied from hollow octahedral Cu 2 S structures, through small pieces of P-Cu 2 MoS 4 , and finally to thin square-like plates of I-Cu 2 MoS 4 , depending on the concentrations of sodium molybdate and thioacetamide. The XRD data indicated that the Cu 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
(81 reference statements)
0
1
0
Order By: Relevance
“…We emphasize that, unlike MoS 2 , ,, which is centrosymmetric in even layers (when adopting 2H stacking type), Cu 2 MX 4 phases are intrinsically noncentrosymmetric and can produce enhanced SHG effects with increasing thickness. Importantly, Cu 2 MX 4 may undergo a polymorph transformation between two stable stacking phases (namely, P and I phases) distinguished by a (1/2, 1/2, 0) layer shift, which is indeed observed under mild conditions during synthesis, ,,, suggesting the presence of a small energy barrier in interlayer sliding. Although in the Cu 2 MX 4 family the pure single layer or bilayer by exfoliation is still a challenge, it has been observed that the Cu 2 MX 4 nanosheets with a thickness of about 1.0 nm (close to the bilayer thickness) obtained by ion intercalation or ultrasonication do maintain the same stacking patterns as the bulk P/I phases. , Therefore, we foresee that bilayer or multilayer Cu 2 MX 4 may become a novel vdW NLO system to generate sliding-modulated SHG signals.…”
Section: Introductionmentioning
confidence: 90%
“…We emphasize that, unlike MoS 2 , ,, which is centrosymmetric in even layers (when adopting 2H stacking type), Cu 2 MX 4 phases are intrinsically noncentrosymmetric and can produce enhanced SHG effects with increasing thickness. Importantly, Cu 2 MX 4 may undergo a polymorph transformation between two stable stacking phases (namely, P and I phases) distinguished by a (1/2, 1/2, 0) layer shift, which is indeed observed under mild conditions during synthesis, ,,, suggesting the presence of a small energy barrier in interlayer sliding. Although in the Cu 2 MX 4 family the pure single layer or bilayer by exfoliation is still a challenge, it has been observed that the Cu 2 MX 4 nanosheets with a thickness of about 1.0 nm (close to the bilayer thickness) obtained by ion intercalation or ultrasonication do maintain the same stacking patterns as the bulk P/I phases. , Therefore, we foresee that bilayer or multilayer Cu 2 MX 4 may become a novel vdW NLO system to generate sliding-modulated SHG signals.…”
Section: Introductionmentioning
confidence: 90%